Volatile analysis of palm kernel cake for inclusion in pig feed. Issue 1 (1st January 2020) - Kini, Shruthi Gopalkrishna; Ding, Jia Wen; Lim, Kevin; Ong, Wei Li; Ochandiano, Untzizu Elejalde; Ng, Kian-Hong
Abstract : Pig farming is one of the major contributors to the livestock industry. In recent years, palm kernel cake (PKC) has increasingly been used in the feed industry as an alternative source of feed ingredient for pigs. As pigs have a great sense of smell, difference in volatile composition of PKC could affect its acceptance and inclusion rate in pig feed. In this study, a comparative study on the volatile profiles of palm kernel expeller (PKE) and palm kernel meal (PKM) was performed using GC-MS coupled with dynamic headspace (DHS) sampling techniques. Our aim is to understand the contribution of geographical origin, processing technology and moisture content to the volatile profiles of PKE and PKM by analysing a total of 56 samples using GC-MS-DHS. Using data analytics, we have obtained a 'volatile fingerprint' of PKE and PKM sourced from different processing plants. We have also gained insight into the potential odour-active compounds in palm kernel cakes of different processes. These results provide scientific basis for the development of more palatable and economical animal feed involving palm kernel cake.